The Impact Of Profitability Ratio Towards Stock Returns Of Consumer Products & Services Sector In Malaysia - Muhammad Zahid, Musa (2019)
Equity investing offers some substantial returns together with the risk associated with it. As a diversification method in investing, it requires some basic and advanced analysis in searching the real value of the listed equity in stock exchange. Financial statement analysis provides the investor with historical performance and a snapshot of current performance of the firms for the underlying stocks. As most of the financial literature focusing on the established and matured market such as in United States, how will the information of financial positions for companies benefited the investors in a smaller and emerging market like Bursa Malaysia Stock Exchange? The purpose of this study is to examine the impact of the financial ratios, focusing on the profitability ratio and its selected components on the returns of the Shariah-approved stocks in the Consumer Products & Services sector in Bursa Malaysia Stock Exchange. The result showed that the profitability ratio showed an overall significant relationship in explaining the stock returns. Further, some components of the ratio were able to explain the returns individually with either a positive or negative effect. This research contributes to the available literature in local Shariah-approved equity research as well as to the investing community. It suggests that market analysts and decision makers in investing community should include the analysis of profitability ratio together other variables in their analysis of investment. Other than that, companies should be focusing more on its internal factor such as the company’s assets in order further increase the operating profit.